Pernikahan Adat Karo sebagai Ide Penciptaan Karya Seni Lukis - Bremana Adriansyah; Insanul Qisti Barriyah; Moh. Rusnoto Susanto; Dwi Susanto (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The purpose of this creation is to develop, introduce, the culture or custom of karo marriage in the form of painting. And can implement it in the form of painting so that it can be enjoyed by the community without having to wait for the moment of the Karo traditional wedding directly. The method of creating this work uses the Exploration method, including; idea exploration, concept exploration, form exploration, media exploration, technical exploration, aesthetic exploration and data analysis, namely primary data and secondary data. The embodiment of this work is in the form of paintings with canvas as the main media with sizes ranging from 70 X 90 Cm, 100 X 100 Cm, to 150 x 150 Cm. The creation of this painting is to implement and tell stories about the Karo traditional wedding in North Sumatra. It is hoped that this painting can introduce and become an educational medium for audiences who do not know this custom or culture. Keywords: Wedding, Karo Culture, Creation Idea, Art, Painting